Torrefaction of palm pressed fibre in a fixed bed reactor / Muhammad Farhan Jamdi, Dr Azrinawati Mohd Zin and Dr Alina Rahayu Mohamed - Jamdi, Muhammad Farhan; Mohd Zin, Azrinawati; Mohamed, Alina Rahayu (2020)
The accumulation of the palm pressed fibres which are the wastes and by-products from the palm oil milling industry and the potential to be reused and utilized as potential biofuels have resulted in palm pressed fibre to become an alternative energy to replace the conventional fossil fuel. However, the direct usage of raw biomass as a source of biofuel is not efficient due to its high moisture content and low energy density value. Hence, the pre-treatment of biomass via torrefaction is required before the biomass is used as a biofuel since torrefaction can increase the energy value of the biomass and reduces the moisture content of the biomass. Torrefaction of palm pressed fibre was performed under an inert environment in a fixed-bed reactor. The effects of on the mass yield, torrefaction temperature (200˚-300˚C) and holding times (20, 40, 60 minutes) were investigated. The kinetic parameters for the torrefaction process at different holding times were analyzed by using the Coats-Redfern method. The results showed that the highest value of activation energy obtained was 29.418kJ/mol at 20 min holding time. From the FTIR analysis, it was found that degradation of the hemicellulose, cellulose and lignin occurred during the torrefaction process.